Neurophysiological constraints on the eye-mind link - Reichle, Erik D.; Reingold, Eyal M. (Frontiers in Human Neuroscience, 2013)
Several current computational models of eye-movement control in reading posit a tight link between the eye and mind, with lexical processing directly triggering most “decisions” about when to start programming a saccade to move the eyes from one word to the next. One potential problem with this theoretical assumption, however, is that it may violate neurophysiological constraints imposed by the time required to encode visual information, complete some amount of lexical processing, and then program a saccade. In this article, we review what has been learned about these timing constraints from studies using ERP and MEG. On the basis of this review, it would appear that the temporal constraints are too severe to permit direct lexical control of eye movements without a significant amount of parafoveal processing (i.e., pre-processing of word n+1 from word n). This conclusion underscores the degree to which the perceptual, cognitive, and motor processes involved in reading must be highly coordinated to support skilled reading, a par excellence example of a task requiring visual-cognitive expertise.